Effect of statins on neurological functional outcomes in critically ill adult patients with traumatic brain injury: a systematic review and meta-analysis - Ryan Zarychanski; François Lauzier; Shane W English; Lynne Moore; Alexis F Turgeon; Daniel F McAuley; Olivier Costerousse; Chartelin Jean Isaac; Marc-Aurèle Gagnon; Charles Veillette; Mauricio Umana; Patrick Lawler (BMJ Open)
Background Statins are considered a promising therapy in traumatic brain injury (TBI) because of their role in mediating inflammatory injury and other endothelial properties. Whether they can improve patient outcomes is unknown.Objectives To evaluate the effect of statins in critically ill patients with TBI.Design Systematic review and meta-analysis of randomised controlled trials.Eligibility criteria Trials of adult patients with acute moderate or severe TBI.Methods We searched Medline, Embase, Cochrane Central and Web of Science databases for trials comparing the use of any statin with placebo or other interventions. Our primary outcome was the Glasgow Outcome Scale (GOS or GOS extended); secondary outcomes were mortality, intensive care unit (ICU) and hospital length of stay. We used inverse variance random-effects models to calculate risk ratios (RR) and weighted mean differences. We assessed the risk of bias of trials using the Cochrane risk of bias assessment tool and the presence of statistical heterogeneity using the I2 index. Levels of evidence for summary effect measures were evaluated using Grading of Recommendations Assessment, Development and Evaluation methodology.1Results Of the 2418 retrieved records, 7 trials met our eligibility criteria. Three studied simvastatin, and four studied atorvastatin. The duration of the intervention ranged from 2 to 10 days, and outcomes were assessed between ICU discharge and 6 months. Five trials were considered at high risk of bias. We observed no statistically significant association between statins and the GOS (RR 0.42; 95% CI, 0.14 to 1.22; two trials; n=84, I2=0%; very low certainty) or mortality (RR 0.59; 95% CI, 0.25 to 1.44; three trials; n=160, I2=0%; very low certainty). No significant effect was observed for ICU length of stay, while hospital length of stay was evaluated in one trial showing shorter duration.Conclusion We found no conclusive evidence supporting the use of statins in critically ill adult patients with TBI at this time. Nevertheless, the trials were limited, and wide confidence intervals resulted in significant uncertainty of the findings. A potential benefit cannot be ruled out, underscoring the need for a larger, well-designed trial.PROSPERO registration number CRD42023421227.